The investigation of the prevalence of condylar degenerative changes and its relationship with disc displacement in the magnetic resonance images of the patients with temporomandibular joint disorders (Annals of Medical Research, 2021)
Aim: The purpose of this study is to investigate the relationship between TMJ disc displacement and chondylar degenerative changes.Material and Methods: The MRIs of 182 TMJs belonging to 91 patients with TMD were evaluated. TMJs were distributed into three groups according to the disc positions as normal disc position (Group 1, n=39), disc displacement with reduction (Group 2, n=49) and disc displacement without reduction (Group 3, n=94). Condylar degenerative change is diagnosed according to presence or absence of erosion, sclerosis, flattening and osteophyte encountered in MRI. When more than one type of degenerative change was observed, the joint was determined to have degenerative changes.Results: The results of MRI evaluation of 182 TMJs revealed Group 1, Group 2 and Group 3 in 39 (21.4%), 49 (26.9%) and 94 (51.6%) joints, respectively. No degenerative condyle was found in 107 (58.8%) joints whereas degenerative condylar changes were encountered in 75 (41.2%) of 182 TMJs by the MRI evaluation. Condyle degeneration was detected in 2 (5.1%) of the joints with normal disc position whereas 6 (12.2%) and 67 (71.3%) of the joints with reducing and non-reducing disc displacement revealed condyle degeneration, respectively.Conclusion: A statistically significantly higher rate of condyle degeneration was encountered in the joints with disc displacement without reduction than the joints with disc displacement with reduction and normal disc position. Advancing disc displacement causes condylar degenerative changes.Keywords: Temporomandibular joint disorders; magnetic resonance imaging; disc displacement; degenerative changes.
Keywords: Temporomandibular joint disorders; magnetic resonance imaging; disc displacement; degenerative changes.